Dehydration of 1, 5‐Pentanediol over CeO2‐MeOx Catalysts. Issue 20 (11th September 2018) - Gnanamani, Muthu Kumaran; Martinelli, Michela; Badoga, Sandeep; Hopps, Shelley D.; Davis, Burtron H.
Abstract: The dehydration reaction of 1, 5‐pentanediol was performed over CeO2 and modified CeO2 (CeO2 −MnOx, CeO2 −ZnO, CeO2 −MgO, CeO2 −CaO, CeO2 −Na2 O) catalysts in a fixed‐bed tubular reactor at 350 °C and an atmospheric pressure. The undoped CeO2 produced a mixture of the products containing mainly 4‐penten‐1‐ol, 1‐pentanol, cyclopentanol, cyclopentanone and tetrahydropyran‐2‐one from 1, 5‐pentanediol, while additions of MgO, MnOx, or ZnO to CeO2 was found to enhance the overall production rate of unsaturated alcohol. On the other hand, more basic metals like CaO or Na2 O tend to decline the dehydration activity of CeO2 . The porous structure of CeO2 did not change appreciably with the addition of metal oxides. Temperature programmed desorption of adsorbed CO2 on an activated catalyst suggest more CO2 remain on the catalyst surface, particularly CeO2 −CaO and CeO2 −Na2 O indicating that fewer defect sites are only available for reaction. The defect sites or oxygen vacancy on CeO2 controls both activity and selectivity for the dehydration of 1, 5‐pentanediol. Abstract : What a site ! The defect sites on CeO2 catalyze both dehydration and cyclization reactions for 1, 5‐pentanediol. The addition of MeOx was found to affect the defect sites formation over CeO2 which greatly impact the activity and selectivity of dehydration of 1, 5‐pentanediol. The CO2 ‐TPD and FTIR analyses indicate more CO2 would remain on the surfaces of ceria after MeOx additions. Moderate basicity is needed for the selective conversion of 1, 5‐pentanediol to unsaturated alcohol on ceria.